Competitive Advantage Through Marketing Strategies - Mittal, Shwetabh (Journal of Commerce and Trade, 2009)
Globalisation has made the world smaller and the markets bigger. The development of marketing is now evolutionary rather than revolutionary. In this competitive age one has to make a clear policy or strategy to be in the market. Strategies refer to determination of a course of action to achieve a desired result. No magic formula exists to prepare for the future. The requirements are excellent insight to understand changing consumer needs, clear planning to focus our efforts on meeting those needs and flexibility. The aim of competitive strategy is to master a market environment by understanding and anticipating the actions of other economic agents, especially competitors. In the present paper, an attempt has been made to analyse the complexities of marketing and the strategies helping the firms to maximize product sales growth and profitability in the competitive, growing market.